Customer-driven management models for choiceless clientele? Business process reengineering in a California welfare agency. (February 2016) - Esbenshade, Jill; Vidal, Matt; Fascilla, Gina; Ono, Mariko
Business process reengineering and lean are increasingly used to restructure public sector work. This article presents a case study of reengineering in a California welfare agency. It finds extensive work intensification and reduced autonomy for the workforce, and deteriorating service for the clientele. Rather than attribute these outcomes as inherent to the business process reengineering model, this article emphasizes how cost cutting and quantitative efficiency were prioritized over worker empowerment and service quality because the organization is a government agency facing severe budgetary pressures under neoliberalism, and the clientele consists of indigent families and individuals who have no choice of an alternative provider.